2007
DOI: 10.1577/m05-209.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Hooking Mortality of Walleyes Caught by Recreational Anglers on Mille Lacs, Minnesota

Abstract: Recent implementation of size-based regulations in recreational fisheries for walleye Sander vitreus have led to more released walleyes and presumably to more losses of released fish. We conducted this study to estimate hooking mortality in Mille Lacs, Minnesota, and to determine factors that influence the survival of released walleyes. Volunteers and Minnesota Department of Natural Resources employees sampled walleyes with common angling methods in 2003 and 2004 on Mille Lacs (n ¼ 1,246). Simple hooking morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 29 publications
3
52
1
Order By: Relevance
“…• C (Hoffman et al 1996;Graeb et al 2005;Reeves and Bruesewitz 2007;Schramm et al 2010). The rapid increase in mortality over this relatively narrow temperature range centered around 18…”
Section: Tournament Effects On Walleye Survival 869mentioning
confidence: 99%
See 1 more Smart Citation
“…• C (Hoffman et al 1996;Graeb et al 2005;Reeves and Bruesewitz 2007;Schramm et al 2010). The rapid increase in mortality over this relatively narrow temperature range centered around 18…”
Section: Tournament Effects On Walleye Survival 869mentioning
confidence: 99%
“…Several factors, including rough-water conditions (Goeman 1991;Suski et al 2005), capture depth (Schramm et al 2010;Talmage and Staples 2011), and hook wounding (Reeves and Bruesewitz 2007), have been suggested or found to influence health or mortality of angler-and tournament-caught Walleyes; however, water temperature appears to be the most pervasive factor. Mortality of angler-caught Walleyes increases with water temperature, but of potentially greater significance is the consistent finding that the probability of mortality increases sharply as water temperature increases from 14…”
Section: Tournament Effects On Walleye Survival 869mentioning
confidence: 99%
“…This is most likely due to the use of artificial baits, which are usually not swallowed deeply. Schill (1996), Schisler and Bergersen (1996), Dubois and Kuklinski (2004) and Reeves and Bruesewitz (2007) observed that the chances of fish swallowing the bait are greatly diminished when artificial baits are used as these are operated actively. Although mortality varies between species, higher mortality rates in general are associated with injury to internal organs and lesions with the presence of bleeding that could be associated with the use of natural bait (Muoneke and Childress, 1994;Bartholomew and Bohnsack, 2005;Broadhurst et al, 2005;Reeves and Bruesewitz, 2007;Alós et al, 2008;Alós, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that catch-and-release mortality rates are strongly influenced by the biological characteristics of the target species (Muoneke and Childress, 1994). However, certain other factors, such as the body part of the fish that was hooked (Pope et al, 2007;Alós et al, 2008), the type of bait (Reeves and Bruesewitz, 2007) and the fighting and handling time (Cooke and Suski, 2004) could also be determinants of mortality rate. Broadhurst et al (2005), studying the mortality rate of the main target species of Australian estuary sport fishing, reported mortality rates between 0 and 36.6% and found that the body part hooked and the time taken to release the fish were the main factors influencing mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation